Development of forensic laboratory networks for international standard accreditation - Seelanan, Parinya (วารสารกระบวนการยุติธรรม, 2024)
The feasibility of international standard accreditation for forensic laboratories can be aligned through the process of preparation, audition and evaluation among internal supporting units and alliances with communal duties. Collaboration within forensic networks becomes more important when the standard guide and operation are involved. The participation level and development of forensic laboratory collaboration were examined as the research objectives. A qualitative study of officers who were engaged in forensic operations and related fields was performed via in-depth interviews. Three groups of key informants, a forensic officer, an academic researcher, and stakeholders from both the government and private sector for 19 persons in total, were interviewed and analyzed. It was found that (1) the participation level of the forensic laboratory collaboration were 4 levels which are academic and service consultation level, academic forming level, examination service level and committee and advised placation level; and (2) action guideline for the development of forensic laboratory collaborative network consists of 2 phases; Phase 1 which is short-term management of well-prepared equipment and competent-based training for the staffs and Phase 2, long-term development. Processes of the collaborative network for the long-term development involve participation in the regulatory and basis of the laboratory, enhancement on forensic examination scopes and measures, and separation of the unit administration from the laboratory facility. The strategy for long-term phase must be supported by interorganizational collaboration under the short-term management. Thus, the process model for standard accreditation guidelines was proposed. In summary, forensic laboratory is encouraged once the participation level and operations are evaluated and qualified. The standard accreditation can be achieved under forensic laboratory network and the participation based on the proposed model.